Network coding : fundamentals and applications - Medard, Muriel; Sprintson, Alex (Academic, 2010)
Network coding is a field of information and coding theory and is a method of attaining maximum information flow in a network. This book is an ideal introduction for the communications and network engineer, working in research and development, who needs an intuitive introduction to network coding and to the increased performance and reliability it offers in many applications. This book is an ideal introduction for the research and development communications and network engineer who needs an intuitive introduction to the theory and wishes to understand the increased performance and reliability it offers over a number of applications. A clear and intuitive introduction to network coding, avoiding difficult mathematics, which does not require a background in information theory. Emphasis on how network coding techniques can be implemented, using a wide range of applications in communications and network engineering Detailed coverage on content distribution networks, peer-to-peer networks, overlay networks, streaming and multimedia applications, storage networks, network security and military networks, reliable communication, wireless networks, delay-tolerant and disruption-tolerant networks, cellular and ad hoc networks (including LTE and WiMAX), and connections with data compression and compressed sensing Edited and contributed by the world's leading experts.